Research on the Uplift Characteristics of Pantographs of High-Speed Trains Under Crosswind Conditions - Meng Zhao; Yaning Duan; Xingbo Lan; Zile Jia (Applied Sciences)
Through the geometric relationships and force analysis of the main components of pantographs on high-speed trains, the coefficients of aerodynamic forces and lift transmission between the pantograph and main components under crosswind conditions were derived. Based on the aerodynamic forces acting on the pantograph at different crosswind speeds, wind angles, and operating speeds, the aerodynamic lift of the pantograph and main components was ultimately determined. The results indicate that the aerodynamic lift of the pantograph is mainly distributed on the bow structure, with the aerodynamic lift of the upper frame all being negative values, while the absolute value of the aerodynamic lift of the lower arm rod is the smallest. The operating speed of the pantograph and the wind angle of the crosswind have a significant impact on the aerodynamic lift of the main components, while the impact of the crosswind speed is relatively small. At the same operating speed of the pantograph, the lower the corresponding crosswind speed, the smaller the aerodynamic lift of the pantograph. The aerodynamic lift of the pantograph tends to decrease gradually with the increase in crosswind speed, and the impact of crosswind speed decreases gradually with the increase in the pantograph operating speed. A comprehensive relationship formula between the aerodynamic lift of the pantograph and the operating speed, crosswind speed, and wind angle is obtained, and the empirical formula for the contact force of the bow net and train operating speed is modified. The research results are of great significance and value for the study and application of lift forces on pantographs under crosswind conditions.